Interação genótipos por ambientes e estratificação de regiões para avaliação de clones de eucalipto - Vergani, Amanda Roberta (2021)
The genotype x environment interaction can change the classification of genotypes in different locations, bringing difficulties to breeding programs and cultivar recommendation. Therefore, it is necessary to group the environments to rationalize the experimentation for clonal recommendation. The objective of this study was to stratify the environments of Dexco company, to group environments with similar genotypic responses, allowing a reduction of environments for experimentation in the Eucalyptus breeding program. Data from 73 clonal tests of Dexco breeding program were analyzed. These experiments contained a total of 1433 clones and were planted in 26 farms, in 15 different cities, in the States of São Paulo and Minas Gerais, distributed in 10 regions. The experiments were planted between 2000 and 2016, in a complete randomized block design, with six replicates and two types of plots, which were lines with five plants, or square with five rows by five plants, where only the nine central plants were measured. The evaluation age ranged from 2.8 to 6.1 years, when DBH (diameter at breast height) and tree height were measured. The volume per tree was subsequently calculated and divided by the age of measurement, to allow the comparison of all experiments through joint analysis. The genetic parameters and the predictions of genotypic values were obtained by the REML / BLUP procedure, using the R software. Stratification of the environments was performed using Spearman's correlation, dendrogram via cluster analysis with UPGMA and principal component analysis. There was similarity in the results for the ranking of clones for six regions and for two others, forming, therefore, two groups of environments. This could lead to a reduction from 10 to four environments for recommendation of clones and consequently a reduction of the number of regions to evaluate genotypes in the company's breeding program.